Model Pembelajaran Pendidikan Agama Kristen Berbasis Nilai-Nilai Tongkonan untuk Penguatan Identitas Spiritual Generasi Muda Toraja - Pairunan Sapparan; Semuel Salasa; Yakil Vantrisa; Senalia Helsa; Yuri Medison (Sabar : Jurnal Pendidikan Agama Kristen dan Katolik, 2026)
This study aims to develop a Christian Religious Education learning model based on Tongkonan values to strengthen the spiritual identity of Toraja youth amid identity crisis caused by globalization. Using qualitative method with literature study, this research analyzes the integration of Tongkonan philosophical values such as karapasan, kasiuluran, and kasianggaran with theological principles of Christian Religious Education through contextual learning approach and narrative theology. The results show that Tongkonan values have strong resonance with Christian teachings and can be integrated into a learning model comprising five components: theological-cultural foundation, contextual curriculum design, experience-based learning strategies, the role of three educational centers, and authentic evaluation. Implementation of this model has significant implications for strengthening spiritual identity through formation of solid self-identity, authentic moral value internalization, and development of spiritual resilience. This Tongkonan values-based Christian Religious Education learning model bridges the dichotomy between modernity and tradition, making Christian Religious Education more relevant and meaningful for Toraja students by equipping them with a holistic identity as Toraja people who are also followers of Christ.